2012
DOI: 10.1093/eurheartj/ehr481
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular volume imaging by magnetic resonance imaging provides insights into overt and sub-clinical myocardial pathology

Abstract: Extracellular volume fraction imaging can quantitatively characterize myocardial infarction, atypical diffuse fibrosis, and subtle myocardial abnormalities not clinically apparent on LGE images. Taken within the context of prior literature, these subtle ECV abnormalities are consistent with diffuse fibrosis related to age and changes remote from infarction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

30
401
3
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 496 publications
(444 citation statements)
references
References 34 publications
(43 reference statements)
30
401
3
2
Order By: Relevance
“…Although native T1 mapping14 and postcontrast T1 mapping13 CMR have been used to interrogate remote myocardial ECM, the availability of automated extracellular volume fraction (ECV) mapping CMR provides a more robust method for quantifying not only focal fibrosis, but also diffuse interstitial expansion in the myocardium15, 16 given that native and postcontrast T1 maps are coregistered and motion corrected, thereby improving the quality of the generated automated maps 17…”
Section: Introductionmentioning
confidence: 99%
“…Although native T1 mapping14 and postcontrast T1 mapping13 CMR have been used to interrogate remote myocardial ECM, the availability of automated extracellular volume fraction (ECV) mapping CMR provides a more robust method for quantifying not only focal fibrosis, but also diffuse interstitial expansion in the myocardium15, 16 given that native and postcontrast T1 maps are coregistered and motion corrected, thereby improving the quality of the generated automated maps 17…”
Section: Introductionmentioning
confidence: 99%
“…45 There are several studies that showed that T1-mapping is useful in identifying more diffuse forms of fibrosis in the remote myocardium and the peri-infarct area (the acquisition time is faster and the spatial resolution is better). 46,47 The notion of peri-infarct zone ("gray zone") was introduced by Schmidt et al The quantification of the peri-infarcted zone can be made by tracing the endo-and epicardial margins in the short-axis sequence and the hypersignal region. 41 The infarct nucleus is defined as the region from the myocardium with a signal intensity higher than 50%.…”
Section: Assessment Of Myocardial Viabilitymentioning
confidence: 99%
“…51 This is true especially with the changes resulting from pathologies other than MI, where the differences between the normal and affected myocardium are less distinct. 47,[51][52][53] Therefore, the more widespread clinical use of these tissue characterization techniques requires further exploration.…”
Section: Myocardial T1 Mapping and Extracellular Volume (Ecv) Fractionmentioning
confidence: 99%